RANCANG ULANG HEAT EXCHANGER SHELL AND TUBE PADA PRESSURE REDUCING SYSTEM UNTUK COMPRESSED NATURAL GAS KAPASITAS 150 m3/Jam - Ramadhan, Anwar Ilmar; Syawaluddin, Syawaluddin; Diniardi, Ery; Sumiyarsono, Dalil (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Reduce the pressure and reheating CNG, created a tool called a pressure reducing system (PRS) which consists of a pressure reducing regulator, heating CNG or we call this section with heat exchanger and measuring tools or gas meter. In connection with this task, will be discussed on the heat exchanger in the heat of this CNG. In this study, a survey was conducted on the heat exchanger Pressure Reducing System (PRS) is installed with a capacity of 200 m3/h, while the use of CNG for the production process is 150 m3/h. CNG temperature after coming out of the PRS read on the thermometer is at 50ÂºC. From these data it can be concluded that the heat exchanger is greater than the required capacity. In order to get heat exchanger in accordance with the capacity of 150 m3/h will be redesigned according to the capacity. From the data obtained it can be concluded that the pressure reducing system capacity greater use of capacity will value of higher effectiveness at about 90%. As for usage as needed obtained effectiveness of 70%. The advantages that can be drawn is that the efficiency in terms of construction materials and a smaller space than the existing PRS.